2015
DOI: 10.1063/1.4916789
|View full text |Cite
|
Sign up to set email alerts
|

On quantifying the climate of the nonautonomous Lorenz-63 model

Abstract: The Lorenz-63 model has been frequently used to inform our understanding of the Earth's climate and provide insight for numerical weather and climate prediction. climate prediction. Taken together, our results imply that current approaches to climate modeling may be at risk of under-sampling key uncertainties likely to be significant in predicting future climate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
0
13
0
2
Order By: Relevance
“…Both taking temporal statistics and a finite ensemble size have been pointed out there to yield biases in general; and the authors suggested that "ensembles of several hundred members may be required to characterize a model's climate". Daron and Stainforth [51] provided further evidence of the biases and discrepancies between temporal and ensemble-wise statistics, and demonstrated the initial-condition-dependence of "transient" convergence properties of ensembles. Pierini [52] and Pierini et al [53] considered a periodically forced reduced double-gyre model described by four variables and determined sample measures, while Chekroun et al [54] studied the pullback attractor and its measure in a delay differential model of ENSO.…”
Section: Ensemble View In Other Conceptual Modelsmentioning
confidence: 94%
“…Both taking temporal statistics and a finite ensemble size have been pointed out there to yield biases in general; and the authors suggested that "ensembles of several hundred members may be required to characterize a model's climate". Daron and Stainforth [51] provided further evidence of the biases and discrepancies between temporal and ensemble-wise statistics, and demonstrated the initial-condition-dependence of "transient" convergence properties of ensembles. Pierini [52] and Pierini et al [53] considered a periodically forced reduced double-gyre model described by four variables and determined sample measures, while Chekroun et al [54] studied the pullback attractor and its measure in a delay differential model of ENSO.…”
Section: Ensemble View In Other Conceptual Modelsmentioning
confidence: 94%
“…years. Daron and Stainforth ([2015]) and Selten et al ([2004]) and Smith ([1987]) also argue that it is plausible that there is no convergence for prediction lead times of interest, and they underscore this with evidence from Lorenz's 1963 model and a community climate systems model. Furthermore, even if climate models had strong physical measures, projections could not be independent of initial conditions ensembles.…”
Section: Dynamical Conditions Justifying Independence Of Initial Condmentioning
confidence: 99%
“…The research that has been carried out is sobering and suggests that a large number of initial conditions (and not just a few) are needed to reliably estimate projections. For instance, Daron and Stainforth ([2013]) using a low-dimensional nonlinear system that exhibits behaviour similar to that of the atmosphere and ocean found that several hundred initial conditions are needed (see also Daron and Stainforth [2015]; Kay et al [2014]). Similarly, Deser et al ([2012]) perform simulations with one of the CMIP5 models, and argue that large initial conditions ensembles are needed.…”
Section: Projectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…indexed by the parameter λ = (σ, b). Note that the model (6.5) and assumption (6.4) are relevant in some climate models, see for example [9]. In particular, the function r(t) can be a finite sum of sinusoidal functions.…”
Section: The Lorenz Systemmentioning
confidence: 99%